Slip Rate Variation During the Last ∼210 ka on a Slow Fault in a Transpressive Regime: The Carrascoy Fault (Eastern Betic Shear Zone, SE Spain) - Martín-Banda, Raquel; Insua-Arévalo, Juan Miguel; García-Mayordomo, Julián (Frontiers in Earth Science, 2021)
Fault slip rate variability over time is a crucial aspect for understanding how single faults interact among each other in fault systems. Several studies worldwide evidence the occurrence of high activity periods with clustering of events and synchronization among faults, followed by long periods of low activity (super-cycles). The increasing gathering of evidence of these phenomena is making fault hazard models quickly evolving and challenging seismic hazard assessment. However, in moderately active fault systems, a determination of fault slip rates can present great uncertainties, that have to be carefully considered when slip rate histories are determined. In this work, we estimate the variation of slip rate in the last ~210 ky of the NE segment of the left-lateral reverse Carrascoy Fault, one of the main faults forming the Eastern Betic Shear Zone in SE Spain. We study two selected field sites where we have been able to measure offsets and date the sediments along with uncertainties. The first site shows a progressive discordance drawn by different calcretes developed on alluvial deposits. The vertical throw is calculated by modeling the growth of the discordance. The vertical slip rates are estimated dating the deformed calcretes by Uranium Series and by comparing them with a complete regional calcrete dates database compiled from the literature. On the second site, we analyze the geomorphology of different Upper Pleistocene alluvial fans, where three incised channels are offset by the fault, providing the net slip for the last ~124 ky. We discuss about the influence of different factors on the estimate of net slip rates using data from different sources. This analysis highlights the importance of determining an accurate fault geometry and how local data can provide misleading deformation rates. Our results suggest the existence of long periods of low activity disturbed by short high activity periods. Such a pattern of activity along time is defined for the first time in the Eastern Betic Shear Zone, with interesting implications in the seismogenic behavior of the rest of the slow faults within the region.